MICP and Advances towards Eco-Friendly and Economical Applications - Rajasekar, A.; Loo Chin Moy, Charles; Wilkinson, S. (2017)
Biomineralization is a natural process aided by living organisms. Due to its applicability in ground improvement and bioremediation, Microbially Induced Calcite Precipitation (MICP) is an interdisciplinary field of study combining engineering, chemistry and microbiology. Bioremediation has been applied widely for contamination containment or removal, in this case it will be containment. MICP can also be applied to improve the efficiency of insitu bioremediation. Urease is an enzyme which can facilitate increased calcite precipitation. However the production of urease by bacteria and thus the resulting carbonate precipitation are inhibited by environmental factors including calcium concentration, bacterial concentration, pH and temperature. Under good conditions MICP can be used for heavy metal and radionuclide immobilization. However technologies such as bioconsolidation and biocementation require improvement such as time and cost. This paper highlights the application of MICP in addition to suggested improvements to make it more eco-friendly and sustainable.